PENGARUH AIR REBUSAN DAUN MAMPELAS (Teteracera indica) TERHADAP AKTIVITAS MOTORIK MENCIT - Zico Fakhrur Rozi (Scripta Biologica, 2018)
Plants (Tetracera indica) commonly used by communities Musi North Rawas District for a variety of treatments. This study aims to see the effect of the use of leaf memelas to motor movement male mice. This research is true experimental with the design of Post-test only with control group design. 25 male mice divided into 5 groups. P0 was given 0 g leaf mampelas, P1 was given 2 g leaf mampelas, P2 was given 5 g leaf mampelas, P3 10 g leaves mampelas and P4 extra joss 10 mg. Treatment activities for 7 days. The calculation of motor motion is done by performing a series of tests with each of 3 repetitions, which consist of negative geotaxis test, swing test and swimming test. From the result of statistical analysis using Kruskal Wallis test, it is known that the boiled leaf water does not affect the negative geotaxis test (0,33>0,05), does not affect the hanging test (0,57>0,05) and swimming endurance  Based on the above data it can be concluded that boiling water does not affect the influence of motor activity of mice.